Manajemen Strategik Digital Fundrising Badan Amil Zakat Nasional Jawa Barat dalam Meningkatkan Minat Muzakki - Haerani, Siti Zakiah Arfi; Aziz, Ali (Tadbir: Jurnal Manajemen Dakwah, 2022)
This study aims to determine: the strategic management of digital fundrising of the National Amil Zakat Agency (BAZNAS) includes the formulation, implementation, and evaluation of digital zakat fundrising. This research is qualitative by using descriptive method. The technique of collecting data is through the process of observation, interviews, and documentation. The results of the study found that the formulation was carried out by setting goals to achieving targets. The implementation of digital fundrising is carried out by training, updating and developing the system. So that the evaluation of digital fundrising can attract the attention of donors to participate in paying zakat. Through this strategic management of digital fundrising, West Java Baznas succeeded in increasing the interest of muzakki so that muzakki increased.